The application of Basel III in Portugal: previsions based on 2012 and 2013 banking balance-sheets - Silva, Amândio (2015)
The Basel Committee on Banking Supervision (BCBS) introduced new regulations for banking supervision in December 2010, better known as Basel III recommendations that aimed at guaranteeing the solidity of banks worldwide and the mitigation of new banking crises risks. The European Union transposed these directives through the Credit Review Directives IV (CRD IV). Portugal adopted CRD IV by a new decree-law no. 157/2014, on 24 th October 2014, enforced from 24 th November 2014. While individual banks have been given the option of using the internal ratings based method, this study analyses the compliance levels of all Portuguese banking institutions using the standard method, also prescribed by BCBS. Our results show that out of thirteen banks on 31-12-2013 only five banks were in a comfortable position and the remaining eight could not reach the minimum requirements set up by BCBS for 1-1-2014.